Thin‐Film Ferroelectrics. Issue 30 (10th June 2022) - Fernandez, Abel; Acharya, Megha; Lee, Han‐Gyeol; Schimpf, Jesse; Jiang, Yizhe; Lou, Djamila; Tian, Zishen; Martin, Lane W.
Abstract: Over the last 30 years, the study of ferroelectric oxides has been revolutionized by the implementation of epitaxial‐thin‐film‐based studies, which have driven many advances in the understanding of ferroelectric physics and the realization of novel polar structures and functionalities. New questions have motivated the development of advanced synthesis, characterization, and simulations of epitaxial thin films and, in turn, have provided new insights and applications across the micro‐, meso‐, and macroscopic length scales. This review traces the evolution of ferroelectric thin‐film research through the early days developing understanding of the roles of size and strain on ferroelectrics to the present day, where such understanding is used to create complex hierarchical domain structures, novel polar topologies, and controlled chemical and defect profiles. The extension of epitaxial techniques, coupled with advances in high‐throughput simulations, now stands to accelerate the discovery and study of new ferroelectric materials. Coming hand‐in‐hand with these new materials is new understanding and control of ferroelectric functionalities. Today, researchers are actively working to apply these lessons in a number of applications, including novel memory and logic architectures, as well as a host of energy conversion devices. Abstract : Over the last 30 years, studies of epitaxial thin‐film ferroelectrics have driven advances in the synthesis, characterization, and understanding of ferroelectric polarization, realizing new ferroelectric order, ferroelectric materials, and applications. A broad look at the field of thin‐film ferroelectrics is provided, connecting early questions motivating researchers to open questions for the coming decades.